The Effectiveness of Learning Motivation on Science Literacy in Elementary School Students - Anisya Fitriani; Putri Melianti; Adinda Wulan Fitriyah (CV. Akademi Merdeka, 2026)
This study aims to analyze the relationship between learning motivation and science literacy in primary school students. Motivation is an important factor in learning, while science literacy plays a role in developing critical and analytical thinking skills. Using a quantitative approach and correlational survey design, data were obtained from a sample size of 50 students (n = 50) from five public elementary schools in Cirebon, Indonesia. The research instrument consisted of a Likert scale questionnaire to measure the level of motivation as well as a written test to assess science literacy. The results of descriptive statistical analysis showed that students' motivation level was high, with an mean score of 31.82 out of 40. In contrast, science literacy was in the medium category, with an mean score of 16.02 out of 26. The correlational findings indicated that high motivation does not always go hand in hand with improved science literacy. This suggests that internal motivation needs to be balanced with relevant and contextualized learning strategies. Thus, effective science education demands an integrated approach that not only facilitates students' affective aspects but also enriches learning experiences through explorative and meaningful methods. The main contribution of this study lies in emphasizing the importance of integration.